An improved RSA cryptosystem based on thread and CRT / Saheed Yakub Kayode and Gbolagade Kazeem Alagbe - Yakub Kayode, Saheed; Kazeem Alagbe, Gbolagade (2017)
This paper proposes an efficient approach to improve Rivest Shamir Adleman (RSA) algorithm using parallel technique. RSA public-key cryptosystem has been the most popular and interesting security technique for majority of applications such as internet protocols, secure internet acces and electronic commerce. The main bottleneck of RSA algorithm is that they are slower compared to symmetric cryptography key alternatives simply because of their foundation in modular arithmetic. Hence, how to make a more efficient and faster implementation of Rivest Shamir Adleman algorithm (RSA) is a great concern to researchers in the field of cryptography. In this paper, we propose a parallel implementation technique using Chinese Remainder Theorem and thread on encryption and decryption operation in RSA when files are to be encrypted and decrypted. Also, in our method, the key size is extended from 1024 bits to 2048 bits in length to provide a good level of security, since 1024 bits key size is no more appropraiate for protecting data. We use a parallel technique that divides RSA power process into seperate threads and employs the use of Chinese Remainder Theorem (CRT) to decrease the time required for both encryption and decryption operation. Java programming language is used to implement the algorithm. Experimental results indicate that as the thread level increases, the encryption and decryption time, which is the most time consuming operation, decreases which shows an improved speed of the RSA cryptosystem.The proposed implementation has a great potential to effectively deal with the RSA algorithm slow speed.